The Influence of Leadership Style and Organizational Culture on Employee Performance (A Case Study at Otanaha General Hospital, Gorontalo City) - Nazlyzya Lapatta; Yohanes Temaluru (Budapest International Research and Critics University, 2023)
This study aims to determine the effect of leadership style on employee performance. The influence of organizational culture on employee performance. The influence of leadership style and organizational culture together on employee performance. This study uses a quantitative method with the type of explanatory research. The population in this study were all employees who worked at Otanaha Hospital, Gorontalo City, namely 270 people. The data collection method in this study uses probability sampling, with random sampling technique. Then set the sample in this study as many as 161 respondents. The method of data analysis in this study used simple regression analysis with the SPSS version 24. The results showed that leadership style had a positive influence on employee performance at Otanaha Hospital, Gorontalo City. Organizational culture has a positive influence on employee performance at Otanaha Hospital, Gorontalo City. Leadership style and organizational culture together have an influence on employee performance at Otanaha Hospital, Gorontalo City.